Infants exposed to maternal type 1 diabetes: intrauterine epigenetic modifications and neurological development - González-González, Nieves Luisa; González-Dávila, Enrique; Castro-Conde, José Ramón; González-Campos, Candelaria; Orribo-Morales, Olivia; Flores, Carlos; Lorenzo-Salazar, José Miguel; González-Montelongo, Rafaela; Muñoz-Barrera, Adrián; Padrón-Pérez, Erika; Villalba-Martín, Nazaret; Acevedo-Arozena, Abraham; et al. (Frontiers in Endocrinology, 2026)
BackgroundThe relationship between the neurodevelopment in infants exposed to maternal Type-1 diabetes and changes in fetal DNA methylation has not yet been investigated.AimThis hypothesis-generating study, we aimed to determine whether neurodevelopmental outcomes in offspring from mothers with Type-1 diabetes are associated with intrauterine epigenetic changes in fetal DNA.Material and MethodsWe conducted a prospective, pilot case-control study, comparing infants exposed to maternal Type-1-diabetes with control infants. Cord blood DNA samples were analyzed using the TruSeq-Methyl-Capture-EPIC-Kit, covering over 3.3 million CpGs. The Bayley-III Scales were used to assess infant neurodevelopment, and the scores were correlated with the newborn DNA methylation data.ResultsIn infants exposed to maternal diabetes, we identified 108 differentially methylated genes enriched in pathways crucial for neurodevelopment: Vocal, Imitative and Observational Learning, Synapse Organization, and Neurogenesis. The greatest methylation differences were observed in differentially methylated regions (DMRs) annotated to key neurological genes: MYT1L (21.61%, q=1.97E-07), NRXN1 (12.30%, q=5.04E-75), SHANK3 (11.62%, q=9.81E-06) and KIRREL3 (7.35%, q= 1.53E-23). Both, NRXN1 and SHANK3, were enriched across all identified neurodevelopmental pathways. At two years of age, the infants exposed to maternal Type-1 diabetes scored significantly lower on the Bayley-III Scales across the cognitive, language, and motor domains. Methylation values across loci annotated to ten neurodevelopment-associated genes were linked to Bayley-III cognitive, language, and/or motor domain scores—with MYT1L and NRXN1 showing significant correlation with the Bayley-III language domain score.ConclusionsWhile further confirmation is needed, we provide the first results supporting the hypothesis that neurodevelopmental alterations observed in offspring of mothers with Type-1 diabetes are potentially associated with DNA methylation changes during intrauterine life which can be identified at birth.